2016
DOI: 10.1093/eurheartj/ehw509
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of stroke in chronic heart failure patients with preserved ejection fraction, but without atrial fibrillation: analysis of the CHARM-Preserved and I-Preserve trials

Abstract: AimsThe incidence and predictors of stroke in patients with heart failure and preserved ejection fraction (HF-PEF), but without atrial fibrillation (AF), are unknown. We described the incidence of stroke in HF-PEF patients with and without AF and predictors of stroke in those without AF.Methods and resultsWe pooled data from the CHARM-Preserved and I-Preserve trials. Using Cox regression, we derived a model for stroke in patients without AF in this cohort and compared its performance with a published model in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 37 publications
(36 reference statements)
3
43
0
2
Order By: Relevance
“…[32] They have found that patients with HFREF and HFPEF share similar risk factors for stroke. [32] In addition, they have shown that the risk model derived from the HFREF cohort predicts stroke in patients with HFPEF with comparable c -index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32] They have found that patients with HFREF and HFPEF share similar risk factors for stroke. [32] In addition, they have shown that the risk model derived from the HFREF cohort predicts stroke in patients with HFPEF with comparable c -index.…”
Section: Discussionmentioning
confidence: 99%
“…[32] They have found that patients with HFREF and HFPEF share similar risk factors for stroke. [32] In addition, they have shown that the risk model derived from the HFREF cohort predicts stroke in patients with HFPEF with comparable c -index. [5, 32] Similarly, our study did not find any significant differences in the ability of the CHA 2 DS 2 -VASc-HK 2 score in predicting TE among patients with HFREF and HFPEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(HF) due to the accumulation of collagen fibres, such that patients with AF have HF with a preserved ejection fraction (HFpEF) rather than HF with reduced ejection fraction (HFrEF), accounting for 30% of cases. [5][6][7] These findings suggest that the atrial fibrosis is associated with collagen metabolism and is involved in the mechanism of AF. Furthermore, hyperhomocysteinemia is a pathological feature in the aetiology of atrial fibrosis, although the underlying mechanisms remain unclear.…”
mentioning
confidence: 81%
“…Среди причин смерти пациентов с ХСН-СФВ большую долю занимают жизнеугрожающие нарушения ритма -до 18 % летальных исходов имеют аритмический генез [6]. В исследовании I-Preserve у 6,1 % больных был диагности-рован мозговой инсульт тромбоэмболического проис-хождения на фоне фибрилляции предсердий (ФП), в 26 % случаев наблюдалась внезапная сердечная смерть (ВСС) [7,8]. Следует отметить, что, по данным многочисленных эпидемиологических исследований, основными причина-ми ВСС являются желудочковые нарушения ритма серд-ца (ЖНРС) -желудочковая тахикардия (ЖТ) и фибрил-ляция желудочков [9].…”
Section: Discussionunclassified